Gambaran Pengetahuan Masyarakat Terhadap Penggunaan Produk Pencerah Kulit - Intan Normalita; Ni made ayu Nila Septianingrum; Widarika S anti Hapsari (Journal Syifa Sciences and Clinical Research, 2022)
Beauty in Indonesia is often associated with white and clean skin. based on a report by the Food and Drug Supervisory Agency (BPOM) in 2015 there were 30 types or 17,000 dangerous cosmetic items which turned out to contain hazardous chemicals such as rhodamine B, hydroquinone, retinoic acid, and mercury which are widely contained in face whitening creams. The purpose of this study was to describe the level of public knowledge about the impact of using skin lightening cosmetics in Magelang. This research is an observational descriptive research using cross sectional method and sampling technique using snowball. The research instrument was in the form of a questionnaire distributed via a googleform link. A total of 110 respondents from Magelang City, 46 and 64 respondents from Magelang Regency participated in this study. As many as 80% of female respondents aged 16-25 years who use skin lightening products for 1 to 2 months (24.5%) %) with income 2,000,000 (68.20%) and spend one package of skin lightening products every month ( 37.27%) with an average cost of around Rp. 10,000 – Rp. 200,000 rupiah and the most used up front (83.60%) . Respondents got cosmetics from cosmetic shops (63.60%) and as many as 50% of respondents said their skin color would return to normal if they stopped using lightening creams. Respondents already know that mercury (70%) is one of the harmful substances in whitening creams and its excessive side effects will endanger skin health (95.5%).